Identification of some Fast Growing Leguminous Tree Species for Nitrogen Fixation Studies - Pokhriyal, T. C.; Bhandari, H. C. S.; Negi, D. S.; Chaukiyal, S. P.; Gupta, B. B. (Indian Forester, 1990)
Studies were carried out to screen twenty seven different leguminous, fast growing tree species for nodule formation and nitrogen fixation activity. The nodules add nitrogenase (acetylene reduction) activity was present in all the twelve mimosoid, four Papilionoids species and absent in all the eleven Caesalpinioid species examined under pot culture conditions.